A Literature Review on the Effectiveness of Project-Based Learning in English for Nursing strategies - I'in Noviana; Syaputra Dwi Santoso (UPPM STIKES Pemkab Jombang, 2025)
Proficiency in English is essential for nursing students to communicate effectively in various contexts, yet many face challenges with English for Specific Purposes (ESP) in nursing. Traditional teaching methods often fail to connect theoretical learning with real-world clinical applications. Project-Based Learning (PjBL) has emerged as an effective strategy to bridge this gap by allowing students to work on real-world projects that are directly relevant to their clinical practice. This literature review investigates the effectiveness of PjBL in enhancing English language proficiency and clinical competence in nursing education. A comprehensive search of studies from 2022 to 2025 from Scopus and Google Schoolar was conducted across relevant databases, focusing on keywords such as